Wiping your conscience clean: Investigating the Macbeth effect in individuals with high obsessive-compulsive contamination concerns. Issue 3 (16th July 2018) - Khan, Mahreen; Grisham, Jessica R.
The Macbeth effect is a proposed phenomenon, whereby feelings of immorality activate a desire to cleanse. Extensions of this theory suggest that cleansing alleviates immoral feelings, thus reducing the urge to engage in compensatory behaviors, such as volunteering. We examined the Macbeth effect and volunteerism in undergraduate students with high levels of obsessive-compulsive disorder contamination concerns ( n = 164). Participants underwent an immorality, anxiety, or neutral emotion-induction condition and subsequently cleansed their hands or performed a control task. For participants in the immorality condition, increased ratings of distress were associated with increased accessibility of cleansing words. Furthermore, individuals in the immorality condition who cleansed volunteered for significantly less time than those who did not cleanse. We discuss findings in relation to the literature on the Macbeth effect and mental contamination.